Impacts of land use pattern on transportation and carbon emission in Kaduna City, Nigeria - Zakka Solomon Dyachia, 1971- , author; Ariva Sugandi Permana, supervisor; Mohammad Rafee Majid; Fakulti Alam Bina (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2018)
Thesis (Doktor Falsafah (Perancangan Bandar dan Wilayah)) - Universiti Teknologi Malaysia, 2018